Bridging the gap in genetics: a progressive model for primary to specialist care - Harding, Brittany; Webber, Colleen; Rühland, Lucia; Dalgarno, Nancy; Armour, Christine; Birtwhistle, Richard; Brown, Glenn; Carroll, June C; Flavin, Michael; Phillips, Susan P.; MacKenzie, Jennifer J (Université d'Ottawa | University of Ottawa, 2019)
Abstract Background The rapid expansion of genetic knowledge, and the implications for healthcare has resulted in an increased role for Primary Care Providers (PCPs) to incorporate genetics into their daily practice. The objective of this study was to explore the self-identified needs, including educational needs, of both urban and rural Primary Care Providers (PCPs) in order to provide genetic care to their patients. Methods Using a qualitative grounded theory approach, ten key informant interviews, and one urban and two rural PCP focus groups (FGs) (n = 19) were conducted. All PCPs practiced in Southeastern Ontario. Data was analyzed using a constant comparative method and thematic design. The data reported here represent a subset of a larger study. Results Participants reported that PCPs have a responsibility to ensure patients receive genetic care. However, specific roles and responsibilities for that care were poorly defined. PCPs identified a need for further education and resources to enable them to provide care for individuals with genetic conditions. Based on the findings, a progressive stepped model that bridges primary and specialty genetic care was developed; the model ranged from PCPs identifying patients with genetic conditions that they could manage alone, to patients who they could manage with informal or electronic consultation to those who clearly required specialist referral. Conclusions PCPs identified a need to integrate genetics into primary care practice but they perceived barriers including a lack of knowledge and confidence, access to timely formal and informal consultation and clearly defined roles for themselves and specialists. To address gaps in PCP confidence in providing genetic care, interventions that are directed at accessible just-in-time support and consultation have the potential to empower PCPs to manage patients’ genetic conditions. Specific attention to content, timing, and accessibility of educational interventions is critical to address the needs of both urban and rural PCPs. A progressive framework for bridging primary to specialty care through a ‘stepped’ model for providing continuing medical education, and genetic care can was developed and can be used to guide future design and delivery of educational interventions and resources.